2020
DOI: 10.1136/bmjsit-2019-000016
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review comparing computer-assisted and conventional total joint arthroplasty: quality assessment and summary of evidence

Abstract: BackgroundSystematic reviews (SRs) of computer-assisted (CA) total knee arthroplasty (TKA) and total hip arthroplasty (THA) report conflicting evidence on its superiority over conventional surgery. Little is known about the quality of these SRs; variability in their methodological quality may be a contributing factor. We evaluated the methodological quality of all published SRs to date, summarized and examined the consistency of the evidence generated by these SRs.MethodsWe searched four databases through Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…In our CATKA cohort, none had a pulmonary embolism or acute myocardial infarction. Our finding that CATKAs were associated with lower odds of postoperative complications compared with conventional TKAs is further supported by a review by Hasan et al, 7 which found that CATKAs have more favorable functional, radiological, and patient safety outcomes. Greater integration of computer navigation technology in practice may have a notable impact on the overall success of TKAs, by mitigating the odds of serious complications and improving patient outcomes.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our CATKA cohort, none had a pulmonary embolism or acute myocardial infarction. Our finding that CATKAs were associated with lower odds of postoperative complications compared with conventional TKAs is further supported by a review by Hasan et al, 7 which found that CATKAs have more favorable functional, radiological, and patient safety outcomes. Greater integration of computer navigation technology in practice may have a notable impact on the overall success of TKAs, by mitigating the odds of serious complications and improving patient outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…Our study corroborates a growing body of evidence that shows CATKAs are associated with lower odds of postoperative in-hospital complications, but the adoption of this technology does not reflect this. [7][8][9][10][11][12][13][31][32][33][34][35]39,40 In the current study, CATKA represented slightly less than 10% of all TKAs. In another recent study of CATKA trends, modest increases were observed from 2010 to 2017.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Qualitative data were extracted and processed into tables (cholecystectomy, Table A2; colectomy, Table A3; hysterectomy, Table A4; nephrectomy, Table A5; prostatectomy, Table A6). The quantitative data that were extracted from the included reviews are listed The quality of all included systematic reviews and meta-analyses was assessed by means of the AMSTAR 2 quality assessment tool [23][24][25]. Instead of generating an overall score, AMSTAR 2 utilizes a quality rating system [23].…”
Section: Data Extractionmentioning
confidence: 99%
“…[12][13][14] A recent review of the literature showed that computerassisted knee arthroplasty (CAKA) is associated with improved implant positioning compared with conventional KA. 15 Initially very expensive, CAKA technology has evolved significantly in the past few years, especially with the recent introduction of low-cost and the userfriendly handheld navigation systems. With such advancements, wide use of the technology is expected.…”
mentioning
confidence: 99%